IDENTIFIKASI DAN DESKRIPSI MORFOLOGI GAMBIR LIAR (Uncaria Gambir (Hunter) Roxb.) KOTA PEKANBARU - Novita Hera; Ridho Teguh Kurniawan; Ahmad Taufiq Arminudin; Tiara Septirosya (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
Gambier plant (Uncaria gambier (Hunter) Roxb.) Is one of the important annual plants producing sap that is widely used for industrial and pharmaceutical purposes. In the Riau, especially Pekanbaru, there are many wild gambiers that have not been identified and need to be identified and characterized. This study aims to find the location of the plant, identify, describe the morphology and determine the type of gambier plants that grow wild in six sub-districts in Pekanbaru. This research was conducted in October to November 2019 in the Six Districts of Pekanbaru City. The method used is a survey method, with purposive sampling. The parameters observed include the leaves, branches, flowers and fruit. The results showed gambier plants were found in the Districts of Rumbai Pesisir, Bukit Raya, and Lima Puluh, while in the Districts of Sukajadi, Sail and Tenayan Raya there were none. Gambir found in the coastal district of Rumbai on the first point were shrimp type, while on the second and third points were riau type. Gambir found in Bukit Raya District in the first and second points are cubadak, while in the third point they are shrimp. Gambir found in Lima Puluh District at the first point of type cubadak.